2015
DOI: 10.4038/jepsl.v4i2.7862
|View full text |Cite
|
Sign up to set email alerts
|

Linking Plant Diversity and Dietary Diversity of Home Gardens: Examining the Nexus Through Structural Equation Modelling

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Marasinghe et al (2015) found a positive significant relationship between the dietary diversity of the household and the plant diversity of homegardens, suggesting that increasing plant diversity in homegardens may achieve food and nutrition security of households. Marambe et al (2012a) also found that tree species in Bangladeshi, Indian and Sri Lankan homegardens are particularly rich in carbohydrates, vitamin C, riboflavin, iron and vitamin B6, whereas drumstick (pod), sesbania (flower) and guava (raw fruit) were the most nutrient rich.…”
Section: Direct Quantification Of Food Securitymentioning
confidence: 92%
See 3 more Smart Citations
“…Marasinghe et al (2015) found a positive significant relationship between the dietary diversity of the household and the plant diversity of homegardens, suggesting that increasing plant diversity in homegardens may achieve food and nutrition security of households. Marambe et al (2012a) also found that tree species in Bangladeshi, Indian and Sri Lankan homegardens are particularly rich in carbohydrates, vitamin C, riboflavin, iron and vitamin B6, whereas drumstick (pod), sesbania (flower) and guava (raw fruit) were the most nutrient rich.…”
Section: Direct Quantification Of Food Securitymentioning
confidence: 92%
“…This includes delivering a mixture of annual and perennial crops, which provide a range of supplemental nutritious products throughout the year at a low input cost highlighting the land use's status as a marginal farming practice Krishnal and Weerahewa 2014;Marasinghe et al 2015). This connects to the notion that homegardens are the poor land users' safety net or insurance when other agricultural activities fail or income is decreasing.…”
Section: What Is Good About Homegardens In Terms Of Food Security?mentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobs, Aliber & Oyelana (2017) reported that home gardening is used as an area for growing vegetables. There is a relation between a dietary variety of household and plant diversity home gardening (Marasinghe, Edirisinghe & Lokuge 2015).…”
Section: A Introductionmentioning
confidence: 99%